Spatial Distribution of Cedrela Odorata Smaller Trees Affects Forest Regeneration in Exotic Tree Plantations in Central Côte d’Ivoire - Vroh, Bi Tra Aimé; Koné, Abdoulaye (Journal of Tropical Biodiversity and Biotechnology, 2023)
Cedrela odorata L. was introduced as a possible forest restauration species in classified forests at Côte d’Ivoire. Because of its demonstrated invasive behavior in other tropical forests, this study aimed to assess the impact of Cedrela odorata on the regeneration of spontaneous plant species in tree plantations. On the base of Cedrela odorata larger tree densities, two types of forest plantation were considered: Type I (240 stems/ha) and Type II (176 stems/ha). In these plantations, plots with 0.25 ha were chosen to locate each tree with dbh ≥ 2.5 cm, in an orthonormal reference. The tree density, the basal area, the species richness, the Shannon diversity index and the rank-abundance curves were determined considering smaller and larger trees. The horizontal spatial arrangement and Ripley’s K function were performed to understand the spatial relationship between Cedrela odorata smaller trees and those of spontaneous species. The results shown lower spontaneous plant species richness (15-20 species) and diversity (1.15 - 1.43); the dominance of Cedrela odorata smaller trees (43.02 – 62.95 % of all stems). The Cedrela odorata smaller trees and those of other species have dependent spatial distributions; expressed by a spatial repulsion between the two groups up to a distance of 18 m in the most densified forest plantation. This repulsion was related to an aggregated distribution of Cedrela odorata smaller trees in plantation with higher tree density. The study suggests a 170-stems/ha (or lower) of Cedrela odorata planting density for biodiversity establishment improvement outcomes in forest plantations.